Cross-Border Acquisitions and Restructuring: Multinational Enterprises versus Private Equity-Firms - Selva Baziki; Pehr-Johan Norbäck; Lars Persson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2015)
An increasingly large share of cross-border acquisitions are undertaken by private equity-firms (PE-firms) and not by traditional multinational enterprises (MNEs). We propose a model of cross-border acquisitions in which MNEs and PE-firms compete over domestic assets. MNEs' advantage lies in firm-specific synergies and retained earnings, whereas PE-firms are good at reorganizing target firms. Prevailing interest rates do not work in favor of PE-firms, but a lower risk premium and a better financial market development does. Stronger firm-specific synergies, however, favors MNEs. Performing a welfare analysis, we show that a policy of restricting PE-firms from buying domestic assets can be counterproductive.
Keywords: F23; F65; L13; 330; Cross-border; International Restructuring; Ownership Efficiency; Private Equity; M&As